Eddy analysis in the Eastern China Sea using altimetry data - QIN, Dandi; WANG, Jianhong; LIU, Yu; DONG, Changming (Frontiers of earth science, 2015)
Statistical characteristics of mesoscale eddies in the Eastern China Sea (ECS) are analyzed using altimetry sea surface height anomaly (SSHA) data from 1993 to 2010. A velocity geometry-based automated eddy detection scheme is employed to detect eddies from the SSHA data to generate an eddy data set. About 1,096 eddies (one lifetime of eddies is counted as one eddy) with a lifetime longer than or equal to 4 weeks are identified in this region. The average lifetime and radius of eddies are 7 weeks and 55 km, respectively, and there is no significant difference between cyclonic eddies (CEs) and anticyclonic eddies (AEs) in this respect. Eddies’ lifetimes are generally longer in deep water than in shallow water. Most eddies propagate northeastward along the Kuroshio (advected by the Kuroshio), with more CEs generated on its western side and AEs on its eastern side. The variation of the Kuroshio transport is one of the major mechanisms for eddy genesis, however the generation of AEs on the eastern side of the Kuroshio (to the open ocean) is also subject to other factors, such as the wind stress curl due to the presence of the Ryukyu Islands and the disturbance from the open ocean.